2017
DOI: 10.1016/j.chb.2016.09.055
|View full text |Cite
|
Sign up to set email alerts
|

Motivators of online vulnerability: The impact of social network site use and FOMO

Abstract: Continued and frequent use of social network sites (SNS) has been linked to a fear of missing out (FOMO) and online self-promotion in the form of friending and information disclosure.The present paper reports findings from 506 UK based Facebook users (53% male) who responded to an extensive online survey about their SNS behaviours and online vulnerability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
185
0
13

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 271 publications
(245 citation statements)
references
References 35 publications
(43 reference statements)
12
185
0
13
Order By: Relevance
“…Although little research has examined how FoMO may fit in a pathway between SNS use and well-being, one study tested the notion that SNS use may trigger feelings of FoMO, which in turn may reduce well-being. This longitudinal study provided evidence that greater SNS use was related to increased FoMO six months later, which in turn was related to decreased self-esteem (Buglass, Binder, Betts, & Underwood, 2017). Given that much previous research has focused on how existing feelings of FoMO may drive SNS use (Przybylski et al, 2013), this study is important as it provides support for the notion that SNS use may trigger feelings of FoMO which in turn may have negative repercussions for subjective well-being.…”
Section: Fear Of Missing Outmentioning
confidence: 60%
See 1 more Smart Citation
“…Although little research has examined how FoMO may fit in a pathway between SNS use and well-being, one study tested the notion that SNS use may trigger feelings of FoMO, which in turn may reduce well-being. This longitudinal study provided evidence that greater SNS use was related to increased FoMO six months later, which in turn was related to decreased self-esteem (Buglass, Binder, Betts, & Underwood, 2017). Given that much previous research has focused on how existing feelings of FoMO may drive SNS use (Przybylski et al, 2013), this study is important as it provides support for the notion that SNS use may trigger feelings of FoMO which in turn may have negative repercussions for subjective well-being.…”
Section: Fear Of Missing Outmentioning
confidence: 60%
“…There are various possibilities for the sequential ordering of passive SNS use, social comparison, FoMO, and depressive symptoms and self-perceptions. Our primary hypothesis revolves around the notion that SNSs may fuel feelings of FoMO, as passively browsing the positive content that others post online may then trigger the fear that others are having more rewarding experiences than the self (Buglass et al, 2017). Thus, FoMO would follow passive SNS use.…”
Section: The Present Studymentioning
confidence: 99%
“…In addition, this study also found that the relationship between psychopathology (as operationalized by anxiety and depression symptoms and assessed via the Hospital Anxiety and Depression Scale) and negative consequences of SNS use were mediated by FOMO, emphasizing the importance of FOMO in the self-perceived consequences of high SNS engagement. Moreover, other research [75] using 506 UK Facebook users has found that FOMO mediates the relationship between high SNS use and decreased self-esteem. Research with psychotherapists working with clients seeking help for their Internet use-related behaviors also suggested that young clients “fear the sort of relentlessness of on-going messaging (…).…”
Section: 10 Lessons Learned From Recent Empirical Literaturementioning
confidence: 97%
“…Recent research [74,75] has suggested that high engagement in social networking is partially due to what has been named the ‘fear of missing out’ (FOMO). FOMO is “a pervasive apprehension that others might be having rewarding experiences from which one is absent” [76].…”
Section: 10 Lessons Learned From Recent Empirical Literaturementioning
confidence: 99%
“…A study conducted by Buglass, Binder, Betts and Underwood (2016) found that the effects of using social networking sites and the decrease of self-esteem was mediated by Fear of Missing Out (FoMO). Fear of Missing Out is defined as the feeling of discomfort or even the feeling of loss that results from knowing what one's friends are doing, and feeling that those friends have it better than them (Abel, Buff, & Burr, 2016 The higher an individual's Fear of Missing Out, the more immersed the individual will be in social media activities, including in online self-presentation (Alt, 2015).…”
Section: Makara Hubs-asiamentioning
confidence: 99%